Interferon lambda 4 polymorphism affects on outcome of telaprevir, pegylated interferon and ribavirin combination therapy for chronic hepatitis C. Issue 14 (6th May 2014) - Nagaoki, Yuko; Imamura, Michio; Kawakami, Yoshiiku; Kan, Hiromi; Fujino, Hatsue; Fukuhara, Takayuki; Kobayashi, Tomoki; Ono, Atsushi; Nakahara, Takashi; Naeshiro, Noriaki; Urabe, Ayako; Yokoyama, Satoe; et al.
<x xml:space="preserve">Abstract</x> Aim The predictive value of the recently identified interferon‐λ (IFNL)4 polymorphism on the outcome of telaprevir (TVR), pegylated interferon (PEG IFN) plus ribavirin (RBV) combination therapy for chronic hepatitis C is unknown. Methods We assessed predictive factors for sustained virological response (SVR) for TVR, PEG IFN plus RBV combination therapy in 283 genotype 1 chronic hepatitis C patients. IFNL4 polymorphism ss469415590 was analyzed by Invader assay. Results SVR rates for patients with IFNL4 TT/TT genotype were significantly higher than for those with the IFNL4 TT/ΔG or ΔG/ΔG genotypes (93% and 59%, respectively, P < 0.0001). In a multivariate regression analysis, prior treatment history (treatment‐naïve patients or patients who relapsed during prior treatment) (odds ratio [OR], 2.385; P = 0.028), rapid virological response (OR, 6.800; P < 0.0001) and ss469415590 TT/TT genotype (OR, 8.064; P < 0.0001) were identified as significant independent predictors for SVR. In patients with IFNL4 TT/ΔG or ΔG/ΔG genotypes, SVR rates for non‐RVR patients were significantly lower than RVR patients (22% and 75%, respectively, P < 0.0001). Conclusion Analysis of IFNL4 polymorphism is a valuable predictor in patients receiving TVR triple therapy.